(untitled) (PerCursos, 2024)
Over the last ten years, from the PEC das domésticas to law 150/2015, it is still necessary to understand the realities of domestic work and the social and cultural aspects in the process of recognizing the rights of domestic workers. The analysis is contextualized through bibliographical research concatenated with data from the Inter-Union Department of Statistics and Socioeconomic Studies (2022), in order to verify the empirical reality of domestic work in Brazil from an intersectional perspective. The empirical results indicate the coloniality of power in social and legal relations, the racial division of labor, the impoverishment of female heads of household and migration to the day laborer category. By analyzing the advances in social and cultural aspects, we can see the mobilization of associations and unions in the intersectional struggle for recognition, the question of resistance and the visibility of domestic work from the private to the public sphere.